Cold resistance of mammalian hibernators ∼ a matter of ferroptosis? - Sone, Masamitsu; Yamaguchi, Yoshifumi (Frontiers in Physiology, 2024)
Most mammals adapt thermal physiology around 37 °C and large deviations from their range, as observed in severe hypothermia and hyperthermia, resulting in organ dysfunction and individual death.A prominent exception is mammalian hibernation. Mammalian hibernators resist the long-term duration of severe low body temperature that is lethal to non-hibernators, including humans and mice. This cold resistance is supported, at least in part, by intrinsic cellular properties, since primary or immortalized cells from several hibernator species can survive longer than those from non-hibernators when cultured at cold temperatures. Recent studies have suggested that cold-induced cell death fulfills the hallmarks of ferroptosis, a type of necrotic cell death that accompanies extensive lipid peroxidation by iron-ion-mediated reactions. In this review, we summarize the current knowledge of cold resistance of mammalian hibernators at the cellular and molecular levels to organ and systemic levels and discuss key pathways that confer cold resistance in mammals.